Catalytic Transfer Hydrogenation of Biomass‐Derived Substrates to Value‐Added Chemicals on Dual‐Function Catalysts: Opportunities and Challenges. Issue 1 (10th December 2018) - Jin, Xin; Yin, Bin; Xia, Qi; Fang, Tianqi; Shen, Jian; Kuang, Liquan; Yang, Chaohe
Abstract: Aqueous‐phase hydrodeoxygenation (APH) of bioderived feedstocks into useful chemical building blocks is one the most important processes for biomass conversion. However, several technological challenges, such as elevated reaction temperature (220–280 °C), high H2 pressure (4–10 MPa), uncontrollable side reactions, and intensive capital investment, have resulted in a bottleneck for the further development of existing APH processes. Catalytic transfer hydrogenation (CTH) under much milder conditions with non‐fossil‐based H2 has attracted extensive interest as a result of several advantageous features, including high atom efficiency (≈100 %), low energy intensity, and green H2 obtained from renewable sources. Typically, CTH can be categorized as internal H2 transfer (sacrificing small amounts of feedstocks for H2 generation) and external H2 transfer from H2 donors (e.g., alcohols, formic acid). Although the last decade has witnessed a few successful applications of conventional APH technologies, CTH is still relatively new for biomass conversion. Very limited attempts have been made in both academia and industry. Understanding the fundamentals for precise control of catalyst structures is key for tunable dual functionality to combine simultaneous H2 generation and hydrogenation. Therefore, this Review focuses on the rational design of dual‐functionalized catalysts for synchronous H2 generation and hydrogenation of bio‐feedstocks into value‐added chemicals through CTH technologies. Most recent studies, published from 2015 to 2018, on the transformation of selected model compounds, including glycerol, xylitol, sorbitol, levulinic acid, hydroxymethylfurfural, furfural, cresol, phenol, and guaiacol, are critically reviewed herein. The relationship between the nanostructures of heterogeneous catalysts and the catalytic activity and selectivity for C−O, C−H, C−C, and O−H bond cleavage are discussed to provide insights into future designs for the atom‐economical conversion of biomass into fuels and chemicals. Abstract : Two for the price of one ! The transformation of bioderived feedstocks into useful chemical building blocks is one the most important processes for biomass conversion. Catalytic transfer hydrogenation (CTH) proceeds under mild conditions with non‐fossil‐based H2 . This Review focuses on the rational design of dual‐functionalized catalysts for synchronous H2 generation and hydrogenation of bio‐feedstocks into value‐added chemicals through CTH technology.